Integrating Humanism Theory into Early Childhood Education Policy in the Digital Era: Opportunities and Challenges of Modernization in Indonesia - Arisanti, Fifi; Uyuni, Tiyana Nur; Kartikasari, Riska; Agustina, Eka; Muti'ah, Muti'ah; Yusuf, Arief Rahman (BUHUTS AL ATHFAL: Jurnal Pendidikan dan Anak Usia Dini, 2025)
This article analyzes the implementation of humanism theory in early childhood education (ECE) policies in the digital era, highlighting the opportunities and challenges arising amid modernization. The main focus is to understand how a humanistic approach, which places children at the center of the learning process, can be effectively applied in the context of technological advancement. The aim of this article is to elucidate the relevance of humanism theory in education policies in the digital age and identify strategies to optimize learning based on humanistic values. This study employs a conceptual approach and literature analysis to explore the interconnection between humanism theory, education policies, and technological developments. Data is analyzed through a critical review of relevant literature, including case studies of education policies from various countries. The findings reveal that applying humanism theory in ECE policies during the digital era can enhance children’s learning experiences through the integration of technology that supports holistic development. However, challenges such as the digital divide and the lack of teacher training in humanism-based approaches pose significant obstacles. The implications of these findings emphasize the importance of designing child-centered policies, providing continuous teacher training, and developing digital tools aligned with humanistic values. This article offers insights for policymakers, educators, and researchers to foster inclusive and future-oriented early childhood education.